2018
DOI: 10.1016/j.nicl.2017.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Delayed access to bilateral input alters cortical organization in children with asymmetric hearing

Abstract: Bilateral hearing in early development protects auditory cortices from reorganizing to prefer the better ear. Yet, such protection could be disrupted by mismatched bilateral input in children with asymmetric hearing who require electric stimulation of the auditory nerve from a cochlear implant in their deaf ear and amplified acoustic sound from a hearing aid in their better ear (bimodal hearing). Cortical responses to bimodal stimulation were measured by electroencephalography in 34 bimodal users and 16 age-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 64 publications
3
30
0
1
Order By: Relevance
“…The results confirmed that the bimodal benefit in lexical tone recognition could be predicted by the low-frequency PTA in the non-implanted ear. The findings were compatible with a recent electroencephalography investigation that revealed bimodal hearing might be more effective in restoring typical cortical organization in children with sufficient acoustic hearing in the non-implanted ear [67].…”
Section: Contributing Variables To Bimodal Benefitssupporting
confidence: 91%
See 2 more Smart Citations
“…The results confirmed that the bimodal benefit in lexical tone recognition could be predicted by the low-frequency PTA in the non-implanted ear. The findings were compatible with a recent electroencephalography investigation that revealed bimodal hearing might be more effective in restoring typical cortical organization in children with sufficient acoustic hearing in the non-implanted ear [67].…”
Section: Contributing Variables To Bimodal Benefitssupporting
confidence: 91%
“…The spectral-temporal region refined by the low-frequency phonetic information from the additional HA might constitute useful glimpsing cues for the bimodal participants to fuse pieces of critical message as acoustic landmarks to 'bootstrap' lexical tone identification. In addition, from the perspective of neuroplasticity, bilateral bimodal hearing could prevent aural preference for the implanted ear and promote the cortical integration of input from bilateral auditory pathways [66,67]. Recently, Polonenko et al [67,68] demonstrated that children with asymmetric hearing loss, who received bimodal input with limited delay (i.e., restricting the duration of unilateral hearing), could reverse abnormal cortical aural preference and recover typical bilateral representations from both ears.…”
Section: Bimodal Benefits For Lexical Tone Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies reveal benefits of bimodal hearing over the use of a cochlear implant alone but continued challenges for listening to speech in noise. Data from some children with better hearing in the non-implanted ear also reveal bimodal improvements in speech perception and spatial hearing that depend on duration of deafness in the poorer ear and access to consistent sound in the better ear 11,12,28,51 . The cohorts of bimodal users represent a very diverse population of implant users 28,5154 .…”
Section: Introductionmentioning
confidence: 96%
“…Data from some children with better hearing in the non-implanted ear also reveal bimodal improvements in speech perception and spatial hearing that depend on duration of deafness in the poorer ear and access to consistent sound in the better ear 11,12,28,51 . The cohorts of bimodal users represent a very diverse population of implant users 28,5154 . Asymmetric hearing loss in children appears to have an increased incidence of auditory nerve hypoplasia, enlarged vestibular aqueducts and positive cytomegalovirus 28,52,54 .…”
Section: Introductionmentioning
confidence: 96%